Geologist - Moening, Kate; Moening, Kate (Minneapolis, MN : Bellwether Media, 2023)
"Simple text and full-color photography introduce beginning readers to geologists. Developed by literacy experts for students in kindergarten through third grade"--
Includes bibliographical references and index.
Ages 5-8
Grades 2-3
Keywords: Geologists -- Juvenile literature; Geology -- Vocational guidance -- Juvenile literature